Inter-Temporal Growth Dynamics in Nigeria: Leveraging on Domestic Investment, Domestic Savings, Foreign Portfolio Investment, Economic Freedom, and Corruption - Agbogun, Oghenekparobo Ernest; Obaro, Victoria Chiamaka; Ezeabasili, Vincent N.; Alajekwu, Udoka Benard (PT. Riset Press International, 2026)
This study investigates the inter-temporal growth dynamics of Nigeria with emphasis on the roles of domestic investment, domestic savings, foreign portfolio investment (FPI), economic freedom, and corruption covering a period of 25 years spanning from 1997 to 2022. Data were sourced from IMF International Financial Statistics (IFS), World Development Indicators-WDI (2022), CBN Bulletin (2022). The empirical study adopted the ARDL model and the TDYL causality test. The ARDL test reported that domestic investment, domestic savings, economic freedom, foreign portfolio investment, corruption exerted negative significant effect on economic growth (ECG) in the short and long run validating the prediction of the sand the wheels theory of corruption. This conformed to the uni-directional causality between CORP and RGDP. The ARDL estimate evidenced that DINV has a positive minimal/insignificant effect on ECG of Nigeria both in the short and long run. Similarly, the TYDL granger causality test confirmed that bi-directional relationship exists between DINV and RGDP. Additionally, domestic savings exerted positive significant effect on ECG in Nigeria both in short and long run. Similarly, the TYDL causality test confirmed that uni-directional causality exist between DSAV and RGDP. Comparably, FPI inflows reported higher positive coefficient value in the long run than in the short run. Similarly, the TYDL granger causality test confirmed that bi-directional causality exist between FPI inflows and RGDP. Again, economic freedom improved ECG in both periods. Similarly, the TYDL granger causality test confirmed that uni-directional causality exist between EFCD and RGDP. Lastly, corruption exerted a significantly negative effect on economic growth in both periods. Hence, the study concludes that for the Nigerian economy to experience outstanding growth, Nigerian investment must be used for productive purposes and not for personal gains. Lastly, the current domestic savings rate should be sustained. Lastly, the Nigerian government should encourage more inflows of foreign capital into the Nigeria economy since induces growth.